Interferon alpha promotes caspase-8 dependent ultraviolet light-mediated keratinocyte apoptosis via interferon regulatory factor 1 - Loftus, Shannon N.; Gharaee-Kermani, Mehrnaz; Xu, Bin; Moore, Tyson M.; Hannoudi, Andrew; Mallbris, Mischa J.; Klein, Benjamin; Gudjonsson, Johann E.; Kahlenberg, J. Michelle (Frontiers in Immunology, 2024)
Ultraviolet (UV) light is a known trigger of both cutaneous and systemic disease manifestations in lupus patients. Lupus skin has elevated expression of type I interferons (IFNs) that promote increased keratinocyte (KC) death after UV exposure. The mechanisms by which KC cell death is increased by type I IFNs are unknown. Here, we examine the specific cell death pathways that are activated in KCs by type I IFN priming and UVB exposure. We identify enhanced activation of caspase-8 dependent apoptosis, but not pyroptosis or necroptosis, in type I IFN and UVB-exposed KCs. In vivo, overexpression of epidermal Ifnk resulted in increased apoptosis in murine skin after UVB treatment. This increase in KC apoptosis was not dependent on known death ligands but rather dependent on type I IFN-upregulation of interferon regulatory factor 1 (IRF1). Together, these data suggest that enhanced sensitivity to UV light exhibited by lupus patients results from type I IFN priming of KCs that drives IRF1 expression resulting in caspase-8 activation and increased apoptosis after minimal exposures to UVB.